Plataforma para desenvolvimento e ensaios em tempo real de estações de recarga rápida de veículos elétricos - Rosa, Jonas Menon da (2024)
Due to increasing concerns about the environment and the decarbonization policy adopted by some countries, the number of electric vehicles is increasing. As a consequence, this translates into an increase in the need for charging infrastructure. Nowadays, in Brazil there is little research and development of equipment that solves this type of market demand. In this sense, this work proposes a real-time testing platform that assists in the development and testing of fast charging stations for electric vehicles, thus allowing the reduction of the development time required for these products to be launched on the market. This work initially presents the contextualization, motivation and definition of the problem to be addressed, followed by a review of the state of the art of charging station technology and current standards in relation to the topic. After understanding the main concepts, the proposed platform is presented along with its advantages and limitations. The results obtained are demonstrated in the last chapter along with a discussion, and finally a conclusion about the work is presented, summarizing the main points covered and how the platform can be improved.